Antimicrobial resistance monitoring: a review of information resources - A. Yu. Kuzmenkov; A. G. Vinogradova (Бюллетень сибирской медицины)
In the last decades, the problem of antibiotic resistance occupies one of the key positions in the global public health system and requires attention from the medical community. Antimicrobial resistance monitoring systems play an important role in tracking the changes in antimicrobial susceptibility for timely correction of antimicrobial therapy. The pharmaceutical industry applies epidemiological data obtained through such monitoring to the creation of new medicines and modification of the antimicrobial substances developed earlier. The article describes some of the international and Russian monitoring systems created at different times. It should be noted that during development, regional-level data are used, while a number of projects present information on a global scale. The completed comparative analysis of available systems revealed both positive aspects and parameters in need of renovation. At the same time, the standardization of collecting basic data for monitoring programs requires significant changes. The majority of systems are able to examine only a limited range of microorganisms and antimicrobials. An important point in the functioning of monitoring systems is a search for the optimal way to visualize output data in tables, interactive maps, and graphics. A significant amount of projects demand further work on the result presentation options. Constant monitoring is a significant component in modern concepts of antibiotic resistance control due to the increasing occurrence of resistant organisms.